2011
DOI: 10.1104/pp.111.181065
|View full text |Cite
|
Sign up to set email alerts
|

SUNRegulates Vegetative and Reproductive Organ Shape by Changing Cell Division Patterns      

Abstract: One of the major genes controlling the elongated fruit shape of tomato (Solanum lycopersicum) is SUN. In this study, we explored the roles of SUN in vegetative and reproductive development using near isogenic lines (NILs) that differ at the sun locus, and SUN overexpressors in both the wild species LA1589 (Solanum pimpinellifolium) and the cultivar Sun1642 background. Our results demonstrate that SUN controls tomato shape through redistribution of mass that is mediated by increased cell division in the longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 38 publications
(59 reference statements)
4
119
0
3
Order By: Relevance
“…Histological observation revealed that the elongated ovary shape of Slelf2 at −4 and 0 DAF was due to longitudinal expansion, whereas the Slelf3 ovary was greatly altered in the proximal region ( Figure 4A). Overexpression of SUN reportedly stimulates ovary elongation and is positively correlated with slender phenotypes in cotyledons, leaflets, and floral organs (Wu et al 2011). In addition, the effects of increased SUN expression after pollination can be observed in developing fruit at 5 DAF, which corresponds to the cell division stage of fruit development (van der Knaap and Tanksley 2001;).…”
Section: Discussionmentioning
confidence: 99%
“…Histological observation revealed that the elongated ovary shape of Slelf2 at −4 and 0 DAF was due to longitudinal expansion, whereas the Slelf3 ovary was greatly altered in the proximal region ( Figure 4A). Overexpression of SUN reportedly stimulates ovary elongation and is positively correlated with slender phenotypes in cotyledons, leaflets, and floral organs (Wu et al 2011). In addition, the effects of increased SUN expression after pollination can be observed in developing fruit at 5 DAF, which corresponds to the cell division stage of fruit development (van der Knaap and Tanksley 2001;).…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression assays demonstrated that IQD1 colocalizes with CaM2 to MT arrays , which suggests a role for IQD1 in linking Ca 2+ -CaM signaling to the regulation of MT-associated processes . Additional support for IQD functions at MTs is indirectly provided by studies in tomato, which showed that duplication of the IQD12/SUN locus causes elongated fruits, altered cell shape, and twisted stems (Xiao et al, 2008;Wu et al, 2011). These phenotypes are reminiscent of plants with mutations in tubulin subunits (Ishida et al, 2007) and several MAPs (Buschmann et al, 2004;Sedbrook et al, 2004).…”
mentioning
confidence: 94%
“…6, A-D), indicating the functionality of the fusion protein. Helical growth aberrations and altered leaf shape were reported for tomato sun lines (Wu et al, 2011) and often are associated with defects in MT functions (Buschmann et al, 2004;Ishida et al, 2007). Moreover, the growth defects are reminiscent of plants overexpressing LONGIFOLIA1/TON1 RECRUITING MOTIF2 (TRM2), which encodes a plant-specific MAP (Lee et al, 2006;Drevensek et al, 2012).…”
Section: Overexpression Of Iqd16 Alters Mt Organization and Cell Shapementioning
confidence: 99%
“…In situ hybridization was performed using digoxigenin-labeled probes as described by Wu et al (2011) with minor modifications. Gene-specific fragments for probe synthesis were amplified by PCR using primers 59-ATGGCTTCCATGAAGTTGC-39 and 59-TCAGATACGAAGAAAATTATTAGGG-39 for OSP and 59-GAACA-GATACCAAACACAAGCAA-39 and 59-AAACCCCAGTTTTCACATGC-39 for ACO4.…”
Section: In Situ Hybridizationmentioning
confidence: 99%